Pendekatan Humaniora Dalam Integrasi Nilai Keislaman (Perspektif Baru Pendidikan Islam Di IAIN Kerinci) - Ravico, Ravico; Siregar, Anggi Desviana; Asbufel, Fatnan; Putri, Auliani Eka (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The transformation of Institut Agama Islam Negeri (IAIN) Kerinci into a center of academic excellence based on the integration of knowledge represents a strategic step to combine Islamic values with modern science. This study explores the history, humanistic paradigm, and strategies for integrating knowledge at IAIN Kerinci. A qualitative method was employed to examine the philosophy, policies, and implementation of knowledge integration through interviews, observations, and document analysis. The findings reveal that IAIN Kerinci strives to create academic distinction by prioritizing local wisdom, Islamic values, and a holistic approach in education, research, and community service. These efforts aim to produce graduates who are intellectually competent, deeply rooted in local cultural values, and capable of competing globally. The study concludes with strategic recommendations to strengthen the institution through curriculum revitalization, faculty quality improvement, and synergistic collaborations with various stakeholders.